The Relationship between Work Duration and Physical Workload with Work Fatigue Levels in Workers at the Fantasy Range Car Workshop - Mayumi Ershanda; Tri Niswati Utami; Meutia Nanda (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2025)
Work fatigue is a problem that is often found in every job, one of which is in a workshop. Kisaran Fantasi Workshop is one of the car repair shops whose work involves muscle and energy. Workers are required to complete repairs according to the queue that exists per day. The queue makes workers have to work late into the night and even rest periods are often used to work when the repair queue does not stop. With poor physical activity and work duration occurring continuously, workers often experience dizziness, frequent yawning, excessive thirst, and a weakening of activity that makes workers often feel like lying down and unable to concentrate. The purpose of this study was to determine the relationship between work duration and physical workload with the level of fatigue in workers at the Kisaran Fantasy Car Workshop. This research is descriptive quantitative research with a Cross Sectional approach. The sampling technique used total sampling with a research sample of 55 respondents. Data collection instruments used questionnaires, observations and interviews. Data were analyzed with Univariate and Bivariate analysis. Statistical test using Chi-Square test with significance α = <0.05. The results showed that there was a relationship between work duration (P value = 0.000) and physical workload (P value = 0.000) with the level of job fatigue in workers at the Kisaran Fan Car Workshop.